Diagnostic accuracy of Xpert MTB/RIF and Xpert ultra tests in pulmonary and extrapulmonary tuberculosis compared to Löwenstein-Jensen culture - Miguel Hueda-Zavaleta; Juan Gomez-; Claudia Barletta-Carrillo; Cinthya Flores-Flores; Nilver Piscoche-Botello; Cecilia Miranda-Visalot; Ada Mendoza-Farro; Sujey Gomez-Colque; Álvaro Taype-Rondán; Cesar Copaja-Corzo (Elsevier, 2024)
Background: Tuberculosis (TB) is one of the leading causes of death worldwide. However, an accurate diagnosis contributes to timely treatment, reducing its adverse consequences. The aim of this research was to determine the diagnostic accuracy of the molecular test Xpert MTB/RIF and Xpert MTB/RIF Ultra (Xpert Ultra) for the diagnosis of pulmonary and extrapulmonary TB compared to Löwenstein-Jensen culture. Methods: We conducted a cross-sectional study of diagnostic accuracy. We included samples from patients who attended a Peruvian laboratory between 2011 and 2022. The index test was the Xpert MTB/RIF and Xpert Ultra and the reference standard was Löwenstein-Jensen solid culture for Mycobacterium tuberculosis. We calculated sensitivity, specificity, and positive and negative likelihood ratios. Results: We evaluated 1023 samples, of which 737 were pulmonary samples, 197 tested positive for the Xpert MTB/RIF and Xpert Ultra tests; and 151 tested positive for culture. The Xpert (MTB/RIF and Ultra) showed a joint sensitivity and specificity of: 97 % (95%CI: 93-99) and 93 % (95%CI: 91-95) in pulmonary samples, 100 % (95%CI: 29.2-100) and 98.3 % (95%CI: 94.1-99.8) in cerebrospinal fluid, 66.7 % (95%CI: 22.3-95.7) and 96.8 % (95%CI: 91-99.3) in pleural fluid, 100 % (95%CI: 15.8-100) and 94.3 % (95%CI: 80.8-99.3) in urine. For the detection of pulmonary TB, the Xpert MTB/RIF had a sensitivity and specificity of 97.1 % (95%CI: 89.9-99.6) and 95.6 % (95%CI: 92.9-97.5) and the Xpert Ultra of 97 % (95%CI: 88.5-99.6) 89.5 % (95%CI: 84.9-93.1) respectively. Conclusion: Our results suggest that the Xpert MTB/RIF and the Xpert Ultra are tests with high diagnostic performance for the detection of pulmonary TB and adequate specificity in pulmonary, cerebrospinal fluid, pleural, and urine samples. However, the results for other samples were imprecise.